2013
DOI: 10.1016/j.jviromet.2013.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and sensitive detection of varicella zoster virus in saliva of patients with herpes zoster

Abstract: VZV reactivation produces zoster (shingles) which may be further complicated by meningoencephalitis, myelopathy, vasculopathy and multiple ocular disorders. Importantly, these neurological and ocular complications of VZV reactivation can occur without rash. In such instances, virological verification relies on detection of VZV DNA or anti-VZV IgG antibody in cerebrospinal fluid (CSF), or less often, the presence of VZV DNA in blood mononuclear cells or anti-VZV IgM antibody in serum or CSF. If VZV were readily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…We developed a rapid saliva-based assay to detect VZV DNA that provided a significant increase in DNA yield and reduced sample processing time from 6 h to 1 h. 6 In the present study, we initially showed that VZV was cell associated in saliva cells isolated from patients with active shingles. We then focused on determining the type of cells in saliva that VZV is associated with and localization of VZV within the cells.…”
mentioning
confidence: 73%
“…We developed a rapid saliva-based assay to detect VZV DNA that provided a significant increase in DNA yield and reduced sample processing time from 6 h to 1 h. 6 In the present study, we initially showed that VZV was cell associated in saliva cells isolated from patients with active shingles. We then focused on determining the type of cells in saliva that VZV is associated with and localization of VZV within the cells.…”
mentioning
confidence: 73%
“…For laboratory diagnosis of VZV infection, the following approaches are currently most useful: PCR on material from skin vesicles (submitted as swabs, fluid or scabs 102104 ), saliva 90,102,103,105107 and cerebrospinal fluid if neurological symptoms or signs are present 91,92,108,109 . Detection of VZV antigens by direct immunofluorescence from vesicles is also rapid and specific, although less sensitive than PCR 110 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…Finally, some may question whether saliva VZV DNA detection by using the centrifugated cell pellets of saliva or the concentrated saliva fluid may be useful for early diagnosis. Indeed, the recent study demonstrated that VZV DNA was abundant in the pelleted fraction of saliva because VZV in saliva is cell‐associated . So, further studies are needed in this area.…”
Section: Discussionmentioning
confidence: 99%